PENERAPAN PENDEKATAN SAINTIFIK BERBANTUAN ASSEMBLR EDU DALAM MENINGKATKAN PEMAHAMAN KONSEP IPA PADA MATERI FOTOSINTESIS SISWA SEKOLAH DASAR - Annisa, Nur; Iskandar, Sofyan; Nuraeni, Fitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In elementary school, understanding the concept of science is important to build a thorough understanding. This class action research was conducted to overcome the problem of understanding concepts in photosynthesis material experienced by grade IV students. The reason is that the learning activities carried out are still teacher-centered, lack of application of creative learning approaches and media, lack of learning resources, and no using LKPD in guiding students in learning. Researchers use classroom action research as a research method by applying a scientific approach assisted by Assemblr Edu as a solution to the problems that occur. The subjects studied in this study were grade IV students of SDN Simpangan 06 with a total of 38 students. The instruments used to obtain data are activity observation sheets and tests of understanding the concept of science on photosynthetic material. Based on the data from the research conducted, it was concluded that the activity of grade IV students of SDN Simpangan 06 increased, in cycle I obtained a percentage of 75.10% and in cycle II obtained a percentage of 85%. My understanding of the concept of science in photosynthetic matter has increased, in cycle I obtained an average value of 78 and classical completeness of 78.94%. In cycle II obtained an average value of 83.18 and a classical completeness of 89.47%. Thus, the application of a scientific approach assisted by Assemblr Edu can improve the understanding of science concepts in photosynthesis material of elementary school students.   Keywords: assembler edu, conceptual understanding, scientific approach